Anaesthesia in Patients with Cardiac or Respiratory Disease (Res Medica, 2013)
The degree and frequency of difficulties associated with anaesthesia depends primarily on the skill and experience of the anaesthetist. However, with the increase in life expectancy and advance in anaesthesia and surgery, a greater number of patients previously considered unfit are now being submitted to surgical operations. In many of these patients incidental cardiovascular, respiratory or other disease, frequently of long-standing, may present problems in the conduct of anaesthesia. Furthermore, many drugs used in the treatment of these conditions can potentiate or modify the pharmacological actions of anaesthetic, analgesic and muscle relaxant drugs and increase the risk of accidents and complications during and following anaesthesia. I t is clear, therefore, that the degree of anaesthetic risk may be quite unrelated to the extent of the surgical procedure. For example, the quite major operation of gastrectomy in a generally healthy young man is, from the anaesthetist’s point of view, a relatively safe and simple procedure, whereas the extraction of a few teeth in a patient with a history of a recent myocardial infarction or with severe asthma may be fraught with considerable danger. Not infrequently, of course, patients with severe heart or lung disease may require a major surgical operation, either for the treatment of the cardiac or pulmonary disease or for some other serious surgical condition and, in such circumstances, the overall risk is still greater. Although it is often quite impossible to eliminate the anaesthetic dangers associated with concurrent disease or to bring about its rapid and spectacular cure, nevertheless the risk can generally be considerably reduced by careful preparation of the patient before anaesthesia and surgery. Even the knowledge that the disease is present or that the patient is receiving certain drugs can go a long way to reducing the risk of accident by alerting the anaesthetist to the possibility of abnormal reaction to anaesthetic drugs.